Who Is Against Immigration? A Cross-Country Investigation of Individual Attitudes toward Immigrants - Mayda, Anna Maria (The Review of Economics and Statistics, 2006)
This paper empirically analyzes economic and noneconomic determinants of individual attitudes toward immigrants, within and across countries. The two survey data sets used, covering a wide range of developed and developing countries, make it possible to test for interactive effects between individual characteristics and country-level attributes. In particular, theory predicts that the correlation between pro-immigration attitudes and individual skill should be related to the skill composition of natives relative to immigrants in the destination country. Skilled individuals should favor immigration in countries where natives are more skilled than immigrants and oppose it otherwise. Results based on direct and indirect measures of the relative skill composition are consistent with these predictions. Noneconomic variables also are correlated with immigration attitudes, but they don't alter significantly the labor-market results.